ANALISIS RANTAI NILAI (Value Chain) KOPRA DI KAMPUNG EMAUS DISTRIK SAUSAPOR KABUPATEN TAMBRAUW - Wambrauw, Ludia; Vivia A.G. Saragih; Ery Atmodjo (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2024)
The agricultural sector is vital to the Indonesian economy and can be a priority in national development. As a tropical country, Indonesia has a high potential for coconut production. Tambrauw Regency is one of the regencies in West Papua Province, which has coconut plants with various potential. This research analyzes the coconut value chain in Emaus Village, Sausapor District, Tambrauw Regency. Through qualitative and quantitative descriptive analysis methods, primary data was obtained through interviews using questionnaires, while secondary data was obtained from research reports, publications, and other data sources. The research results show that the copra supply chain in Emmaus Village consists of processing farmers, collecting traders, wholesalers, and industrial consumers. The added value calculation in Emmaus Village is carried out by processing farmers and collecting traders. The added value of coconut processing farmers and collectors reached 64.73%, and that of collecting traders was 8.3%. Furthermore, processing farmers obtain a profit level of 100% because no costs are incurred while collecting traders obtain a profit level of 8.3%. Meanwhile, the added value for wholesalers is greater than that of processing farmers and collecting traders, with an income level after deducting raw material purchases of IDR 5,000. The added value plays an important role in determining the profit level of the coconut business. The higher the added value that is successfully generated, the greater the potential profit that can be obtained.